1970
DOI: 10.1042/bj1200831
|View full text |Cite
|
Sign up to set email alerts
|

Determination of high-affinity oestrogen-receptor sites in uterine supernatant preparations

Abstract: An assay method was developed for the determination of high-affinity oestradiol receptors in uterine supernatant preparations. When only high-affinity sites are present in such preparations, or when they predominate, the analysis of the equilibrium between oestradiol and receptor sites based on the Scatchard (1949) plot may be used to determine the dissociation constant of the equilibrium and the molar concentration of the high-affinity sites. When both high-affinity and low-affinity sites are present the Scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The time course for binding in vitro of 17/3-estradiol to its receptor in the lactating mammary gland is typical of those described for other systems (e.g., uterus and breast carcinoma). Both Méster et al (1970) and Feherty et al (1971) reported significant losses of activity at 37°while binding at 0°r equired several hours to reach completion. The latter report suggested an intermediate temperature (30°) to carry out the incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time course for binding in vitro of 17/3-estradiol to its receptor in the lactating mammary gland is typical of those described for other systems (e.g., uterus and breast carcinoma). Both Méster et al (1970) and Feherty et al (1971) reported significant losses of activity at 37°while binding at 0°r equired several hours to reach completion. The latter report suggested an intermediate temperature (30°) to carry out the incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Early in these investigations, it was determined necessary to establish a method of quickly assessing estrogen-binding capacity in a number of different tissue samples. For this purpose, the dextran-coated charcoal method, as originally described by Korenman (1968) and modified by Méster et al (1970), was chosen. While this procedure proved satisfactory for the most part, several modifications were necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we use kitalicoffL=102 s −1 . Estradiol binds its receptor with K D  ∼ 0.1 nM [38] which corresponds to kitalicoffE=104 s −1 . It should be noted that affinities and half-lifes have been reported to vary due to different glycosylations [56], but such details are beyond the scope of this study.…”
Section: Methodsmentioning
confidence: 99%
“…The in¬ tegrity of sulphydryl groups in the HAR is critical; binding is inhibited by SH blocking agents (Shyamala & Gorski, 1969; and see James & Fotherby, 1970;Jensen et al 1971) and the presence of the reducing agent, 2-mercaptoethanol, stabilizes the binding capacity of the protein (Méster et al 1970). …”
mentioning
confidence: 96%
“…Binding is maximal between pH 7 and 8 (Notides, 1970) ; irreversible inactivation takes place outside this range (Notides, 1970;Master et al 1970). It is highly thermolabile but may be stored at -10 CC for up to 2 months without loss of binding activity (Méster et al 1970) ; the effects of freezing and thawing on binding activity have not been studied.…”
mentioning
confidence: 99%